Analisis Yuridis terhadap Pengesampingan Pasal 1266 KUH Perdata dalam Kasus Pengakhiran Suatu Perjanjian Karena Terjadinya Wanprestasi - Mohamad Ali; Mohammad Hifni (Jurnal Hukum Lex Generalis, 2025)
Article 1266 of the Civil Code explains that default by one party does not immediately terminate the agreement, but must first be brought before a judge. However, in its implementation, the parties usually do not pay attention to the provisions of Article 1266 of the Civil Code, so that if a default occurs, the agreement can be terminated unilaterally. The core problem in this article relates to the views of legal experts on the neglect of Article 1266 of the Civil Code and the application of the waiver clause of Article 1266 of the Civil Code based on court decisions. This research is a normative legal study that utilizes secondary data obtained from literature analysis. This article explains that there are differences of opinion among legal experts regarding whether the parties are allowed to ignore Article 1266 of the Civil Code, seen from the characteristics of the legal norms, the situations, and the parties involved in the agreement. Based on the analysis of court decisions by the Author, most judges agree with the application of the waiver clause of Article 1266 of the Civil Code based on Article 1338 paragraph (1) of the Civil Code. Thus, the agreement between the parties regarding the waiver of Article 1266 of the Civil Code in the agreement must be complied with by the parties concerned. Judges who reject the application of the waiver clause of Article 1266 of the Civil Code assume that the action is contrary to the provisions contained in Article 1266 of the Civil Code.